Why Do New Technologies Complement Skills? Directed Technical Change and Wage Inequality - Acemoglu, D. (Quarterly Journal of Economics, 1998)
A high proportion of skilled workers in the labor force implies a large market size for skill-complementary technologies, and encourages faster upgrading of the productivity of skilled workers. As a result, an increase in the supply of skills reduces the skill premium in the short run, but then it induces skill-biased technical change and increases the skill premium, possibly even above its initial value. This theory suggests that the rapid increase in the proportion of college graduates in the United States labor force in the 1970s may have been a causal factor in both the decline in the college premium during the 1970s and the large increase in inequality during the 1980s.